2020
DOI: 10.1038/s41598-020-75256-6
|View full text |Cite
|
Sign up to set email alerts
|

CHA2DS2-VASc score, cerebral small vessel disease, and frailty in older patients with atrial fibrillation

Abstract: The CHA2DS2-VASc score is a validated predictor of ischemic stroke in atrial fibrillation (AF) patients. However, data are limited on whether the CHA2DS2-VASc score is associated with subclinical brain structural changes or physical frailty among older AF patients. We assessed the relationship between CHA2DS2-VASc scores and brain structural changes or physical frailty in AF patients without history of stroke. Overall, 117 patients completed a comprehensive geriatric assessment for physical frailty. In brain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…As expected, studies show a positive correlation between CHA2DS2-VASc score and leukoaraiosis severity. In a study among nonvalvular AF patients aged 65 years or older, total WMH lesion volume was higher in those with increased risk of CHA2DS2-VASc score (n=40) than in those with intermediate risk (score of 1 in men or 2 in women) of CHA2DS2-VASc score (n=9) [ 29 ]. Using the Fazekas scoring system instead of volumetric measures for WMH may be partly the reason for our not finding an association.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, studies show a positive correlation between CHA2DS2-VASc score and leukoaraiosis severity. In a study among nonvalvular AF patients aged 65 years or older, total WMH lesion volume was higher in those with increased risk of CHA2DS2-VASc score (n=40) than in those with intermediate risk (score of 1 in men or 2 in women) of CHA2DS2-VASc score (n=9) [ 29 ]. Using the Fazekas scoring system instead of volumetric measures for WMH may be partly the reason for our not finding an association.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the mechanisms linking FS and CHA2DS2-VASc score in patients with AF are limited [ 36 , 70 ]. The PURE-Rhythm score update noted that the CHA2DS2-VASc score expresses complex clinical status and is inversely correlated with the Short Physical Performance Battery and Frailty Index.…”
Section: Frailty Syndrome and Atrial Fibrillationmentioning
confidence: 99%
“…The prevalence of frailty increases with age and is associated with various adverse outcomes, including falls, disability, long-term care, and death 7 . Moreover, a recent study demonstrated the relationship among the risk of ischemic stroke, cerebral small vessel disease, and frailty 8 .…”
Section: Introductionmentioning
confidence: 99%